Donor‐Derived Trypanosoma cruzi Infection in Solid Organ Recipients in the United States, 2001–2011. Issue 9 (9th July 2013) - Huprikar, S.; Bosserman, E.; Patel, G.; Moore, A.; Pinney, S.; Anyanwu, A.; Neofytos, D.; Ketterer, D.; Striker, R.; Silveira, F.; Qvarnstrom, Y.; Steurer, F.; et al.
Abstract Although Trypanosoma cruzi, the parasite that causes Chagas disease, can be transmitted via organ transplantation, liver and kidney transplantation from infected donors may be feasible. We describe the outcomes of 32 transplant recipients who received organs from 14 T. cruzi seropositive donors in the United States from 2001 to 2011. Transmission was confirmed in 9 recipients from 6 donors, including 3 of 4 (75%) heart transplant recipients, 2 of 10 (20%) liver recipients and 2 of 15 (13%) kidney recipients. Recommended monitoring posttransplant consisted of regular testing by PCR, hemoculture, and serology. Thirteen recipients had no or incomplete monitoring; transmission was confirmed in five of these recipients. Four of the five recipients had symptomatic disease and all four died although death was directly related to Chagas disease in only one. Nineteen recipients had partial or complete monitoring for T. cruzi infection with weekly testing by PCR, hemoculture and serology; transmission was confirmed in 4 of 19 recipients with no cases of symptomatic disease. Our results suggest that liver and kidney transplantation from T. cruzi seropositive donors may be feasible when the recommended monitoring schedule for T. cruzi infection is followed and prompt therapy with benznidazole can be administered.